A NOVEL SELF-POWERED PIEZOELECTRIC THREE-AXIS MEMS MAGNETIC SENSOR - Yeh, Po-Chen; Duan, Hao; Chung, Tien-Kan (My University, 2017)
This paper demonstrates a self-powered piezoelectric three-axis MEMS magnetic sensor. The sensor consists of a silicon diaphragm, a PZT thin film with Pt top and bottom electrodes, and two patterned Ni thick films. When three-axial magnetic fields are applied to the sensor, alternating magnetic forces/torques are induced in two Ni films and consequently corresponding deformation/bending are produced in the diaphragm structure. The deformation/bending of the diaphragm generate the strains in the PZT thin film and thus produce corresponding different piezoelectric voltage responses. The testing results show the sensor successfully senses three-axial magnetic fields and has a decent linearity in the range of 5-70 Gauss.
Keywords: Piezoelectric; magnetic sensor; three-axis; MEMS